(untitled) (Nepal Journal of Obstetrics and Gynaecology, 2018)
Aims: To study etiology of fistula in patient at Shaikh Zaid Women hospital Larkana. Methods: A cross-sectional Survey was conducted at Gynecology and obstetrics wards of Shaikh Zaid Women hospital Larkana. All patients were admitted in outpatient departments along with emergency department were the part of the study. Sample was collected by universal sample technique. Total sample size was of 49 patients. Detailed history regarding fistula formation and its etiology and duration, examination and related investigation carried out in each and every patient. Young and elderly patients both were included. Results: 49 patients were selected, who were admitted and registered at the gynecological and obstetrics wards of Shaikh Zaid Women hospital, out of which 38 patients were found having urinary fistula from which 28 patients were having fistula due to obstetric causes while 10 pts were having fistula due to iatrogenic causes. Moreover, 11 patients were having fecal fistula from them 7 were again due to obstetric causes, 1 patient was having congenital fistula and remaining 3 patients were found having fistulas due to malignancy. Conclusions: Obstetrics fistula is still most common cause of fistula followed by iatrogenic cause. Urinary fistula is more common than fecal fistula.